HUBUNGAN BUDAYA ORGANISASI, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PETUGAS KESEHATAN - Janes Jainurakhma (LPPMK STIKES Widyagama Husada, 2022)
Some aspects of work affect the achievement of job satisfaction. Such as good work motivation, a positive work environment and a good organizational culture will foster a positive attitude in loving work and workers will feel satisfied with the work they do. The purpose of this research is to analyze the relationship of organizational culture, work motivation and work environment to the job satisfaction of health workers in Dlanggu Health Center of Mojokerto district. This research design is observational analytics with a crossectional approach. Independent variables in research are organizational culture, motivation and work environment, while dependent variables are job satisfaction. The research population is all health workers in Dlanggu Health Center 52 employees. The sample was taken with purposive sampling techniques as many as 46 respondents. The data was collected with questionnaire instruments and tested with chi square and spearman rho tests. The results showed that all values of ρ < α so that H1 is accepted means that there is a relationship between organizational culture, work motivation and the work environment to the job satisfaction of health workers in Dlanggu Health Center of Mojokerto district. Management or leadership at Dlanggu Health Center of Mojokerto Regency is expected to improve the application of organizational culture better through the attachment of the role of the organization or puskesmas in fostering morale for officers, in addition, facilities or work environments can be modified more comfortably and complete so that officers can carry out activities in providing services to patients well and officers can also feel comfortabel in working so as to spur better work motivation.